LOW-POWER MULTI-SENSOR EXTENSION FOR WEMOS CONTROLLERS USING MULTIPLEXED ANALOG INPUTS - Zuly Budiarso Budiarso; Muji Sukur; Eddy Nurraharjo; saefurrohman (Jurnal Riset Informatika, 2025)
The increasing demand for low-cost, compact, and energy-efficient IoT systems has highlighted the limitations of microcontroller units (MCUs) such as the WeMOS D1 Mini, which are constrained by a single analog input pin. This is a major challenge for applications that require multiple analog sensors, such as environmental monitoring or smart agriculture. This paper presents a hardware-based solution using the CD74HC4067 16-channel analog multiplexer to expand the analog input capacity of the WeMOS controller. The system architecture allows multiple sensors to share a single analog input managed by digital control lines. The experimental implementation used six Light Dependent Resistor (LDR) sensors to evaluate accuracy, latency, and power efficiency. The results show that sensor reading accuracy remains within ±2% deviation, with an average channel switching latency of 42 milliseconds and only a 5% increase in total power consumption compared to a single sensor system. These results confirm that the multiplexing strategy maintains reliable performance while significantly improving scalability without compromising power constraints. The proposed approach provides a robust, low-power, and low-cost method for multi-sensor deployment on constrained MCUs, enabling broader application in resource-constrained IoT systems. Future developments may include cascading multiple multiplexers and integrating wireless data transmission for remote sensing applications.